Peningkatan hasil belajar matematika melalui pendekatan pmri pada siswa kelas x smk - Harwidi, Dini (Universitas Sebelas Maret, 2020)
This study aims to improve mathematics learning outcomes in determining the trigonometric ratio of right triangles in class X TKKR second semester students of SMK Negeri 2 Godean, Sleman Regency, Yogyakarta Special Region, 2018/2019 academic year through the application of the PMRI approach. This research was conducted at SMK Negeri 2 Sleman Regency. This research is a collaborative classroom action research. The research object was the students of class X SMK Negeri 2 Godean Sleman Regency. Research procedures through planning, implementation, observation and monitoring, and reflection. Data collection techniques through observation, field notes, and written tests. Types of instruments and how to use them with an observation guide. The data analysis technique used qualitative analysis. The results showed that in the implementation of learning to determine the ratio of trigonometry to a right triangle through the PMRI approach in cycle I, students who actively participated in learning were 72.26%. The results of the formative test had an average value of 62.95. In cycle II, students who actively participate in learning are 81.94%. The results of the formative test an average value of 80.48.